Coping with Demographic Change: A Comparative View on Education and Local Government in Germany and Poland - Sackmann, Reinhold; Bartl, Walter; Jonda, Bernadette; Kopycka, Katarzyna; Rademacher, Christian (European Studies of Population,, 2015)
With many OECD countries experiencing a decline in their populations, this book offers a theoretical model of coping with demographic change and examines different strategies that societies have used to come to terms with demographic change. In particular, it details the different ways that Germany and Poland have tried to cope with this challenge and reveals three conflicting strategies: expansion, reduction, and phasing out. Coverage includes: · How and why demographic change was used in Poland to expand the education system · The variance of linkage between demographic change and growth rates in different fields of education in a German Bundesland · Modes of reflexivity and personnel policy in German and Polish municipalities · Effects of demographic change and forms of coping on fiscal capacity and unemployment rates in German municipalities. Coping with Demographic Change examines how and why societies cope with these detrimental effects. It conceptualizes the challenges a society faces as a result of demographic change and focuses on the processes by which actors, organizations and nation-states try to cope with this new situation.